PTU-090 The use of faecal calprotectin as a screening tool for referring patients with possible ibd. (June 2019) - Fernandes, Darren; Mathew, Aarati; Elphick, David
Abstract : Introduction: Faecal calprotectin (FC) has been shown to have high sensitivity and specificity for differentiating between Inflammatory Bowel Disease (IBD) and functional gastrointestinal disorders. However, there are different thresholds for interpreting FC results. The National Institute for Health and Care Excellence (NICE) therefore proposed the role of an intermediate range for values with Turvill et al. suggesting a cut off of >100. At Chesterfield Royal Hospital, no such intermediate range has been determined. The purpose of this study was thus to analyse FC results and referral outcomes to discover if using a cut off value of >100 was adequate in diagnosing IBD. Method: A retrospective analysis was conducted for all patients in Chesterfield who had a FC requested by their GP between July and December 2017. The notes of those referred and seen in clinic were then analysed. Results: 498 patients had a FC performed by their GP. 107 patients were seen in clinic, 58 were female and 49 were male. Ages ranged from 16 years to 89 years with FC results from <8 to 1086. 9 patients in total were diagnosed with IBD. If a cut off FC >100 were used; 42 of these patients would have been referred with 6 being diagnosed with IBD. 65 would not have been referred but 3 would have IBD, giving a sensitivity of 66.67% (95% CI 29.93% to 92.51%) and a specificity of 63.27% (95% CI 52.93% to 72.78%). The positive predictive value of our test would therefore be 14.29% (95% CI 8.93% to 22.07%) with negative predictive value of 95.38% (95% CI 89.02% to 98.14%). Conclusion: Our study has shown that using a cut off value of >100 for FC values will result in a lower sensitivity when compared to data from other groups. However, a larger cohort of patients will need to be retrospectively analysed to determine whether a cut off value for FC of 100 should be used or if it should be lowered in order to improve sensitivity and specificity in diagnosing patients with IBD. In addition, we have discovered that FC testing is being incorrectly performed in patients who meet other diagnostic pathways and so further advice and guidance needs to be given regarding its use.